Avaliação das habilidades auditivas e da percepção de fala em idosos usuários de Aparelho de Amplificação Sonora Individual: esudo piloto - Fonseca, Angélica Biazus Mendonça da (2014)
processing, associated with the decline of working memory and attention. The comprehension of speech is a highly specialized activity and involves the perception and cognition. The objective of this study was to investigate whether the assessment of auditory skills and speech perception in the elderly, new users of Individual sound amplification device, assists in the process of selection and adaptation of AASI. Methods: we selected 15 individuals with sensorineural hearing loss from mild to moderate degree, new users of bilateral hearing aids, aged between 60 and 75 years. The subjects were assessed by means of Duration Pattern Sequence Test (DPST), Dichotic Digits Test (DDT), Differential Limen of Intensity (DLI), Index of Sentence Recognition (ISR) in quiet and in noise, Sentence Recognition Threshold (SRT) in quiet and in noise and by self-evaluation questionnaire auditory handicap for senior citizens (HHIE-S) in two instances: without hearing aid (first evaluation), and after 3 months (2nd evaluation). Results: tests, DLI only in LE, SRT in noise , SRT in quiet and ISR in quiet showed that there were no statistically significant difference between the two evaluations. In the remaining tests there is difference statistically significant between the assessments. Conclusion: The proposed tests may be part of the process of adaptation of the HEARING AID, because they contribute to the extent of satisfaction and performance, allowing the audiologist forward to hearing/cognitive rehabilitation when necessary